Exploratory comparison of auditory verbal hallucinations and other psychotic symptoms among youth with borderline personality disorder or schizophrenia spectrum disorder. Issue 5 (28th November 2018) - Cavelti, Marialuisa; Thompson, Katherine N.; Hulbert, Carol; Betts, Jennifer; Jackson, Henry; Francey, Shona; Homan, Philipp; Chanen, Andrew M.
Abstract : Objective: This study explored phenomenological aspects of auditory verbal hallucinations (AVH) and other psychotic symptoms among youth with borderline personality disorder (BPD). Methods: Sixty‐eight outpatients, aged 15 to 25 years, were categorized into three groups according to their primary Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5) diagnosis and AVH symptom profile; BPD + AVH ( n  = 23), schizophrenia spectrum disorder (SZ) + AVH ( n  = 22) and BPD with no AVH ( n  = 23). Results: No differences in AVH were found between BPD + AVH and SZ + AVH. Compared with SZ + AVH, BPD + AVH scored lower on delusions and difficulty in abstract thinking and higher on hostility. BPD + AVH reported more severe self‐harm, paranoid ideation, dissociation, anxiety and stress than BPD no AVH. Conclusions: This study replicates, in a sample of youth, the finding from studies of adults that AVH in BPD are indistinguishable from those in SZ, when assessed with the Psychotic Symptom Rating Scales (PSYRATS). Clinicians should specifically enquire about AVH among youth with BPD. When present, AVH appear to be an indicator of a more severe form of BPD.